Biology for engineers - Johnson, Arthur T. 1941- (CRC Press, 2011)
"An introductory text on biology from an engineering perspective, this resource elaborates on concepts and technology with an emphasis on the utilization of living things. Rather than treating biology as a science requiring memorization of connections and classifications, the book explores its relevance as an application area for engineering analysis and design. The author takes a broad approach, encompassing everything from genetics and cellular structure to grand ecological systems"--Provided by publisher.